Materials on Turkish Georgians: The process of globalization looks like a huge wave: it threatens to weak and supports to surfers /Tariel Putkaradze, 2011/ - Putkaradze, Tariel; Labadze, Mikheil (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2021)
I think that special actions should be taken in terms of creating present-day database of autochthonous Georgians and Georgian diasporas, those who reside outside borders of Georgia; also analyzing information and providing Georgian national-cultural co-existence opportunities for Georgians living in the foreign countries (Internet gives the best possibilities for realizing those ideas) is of high priority. The autochthonous Georgians mainly live in Trabzon, Artvin and Erzerum territories of Turkish republic (historic places of Lazeti, Livana, Shavsheti, Tao, Erusheti...); We have plentiful compacted residences of Muhajir Georgians in Adafazari, Bursa-Inegoli, Gonen-Kaiseri, Ordu-Patsa and others. The national-state identity of the autochthonous Georgians and Georgian diasporas residing in Turkey are of identical with its characteristic merits. We can separate 5 main groups of Georgians: Integrated citizens in Turkish republic with Georgian originality who did not remember neither their historic mother tongue nor the originality and perceive themselves as Turkish; Integrated citizens in Turkish republic with Georgian originality, who, in spite of communicating into their mother tongue, yet perceive themselves as Turkish; Georgian speech for them is either childhood (not the vernacular!) or the second language; Integrated Georgians in Turkish republic whose vernacular is the Georgian language, but they prefer Turkish (English, German)... as the education language of their children; those have doubled self-perception; Integrated Georgians in Turkish republic who have totally forgotten historic mother tongue, mother-religious, customs, but yet recognize themselves as Georgians in spite of lacking information on their originality. (in some cases some may have preserved Georgian traditional village, color of eyes, kinds of dishes...). That part of Georgians intensively tries to return to their homeland as Georgians; Integrated Georgians in Turkish republic for whom historic mother tongue represent the first language; accordingly, such individuals really perceive themselves as Georgians (“tsare (hot) gurji”, “super gurji”)... Based on the analysis of the materials found out by me in the Turkish republic, we can say that what Turkish Georgians set apart from Kurds and other ethnic group representatives is the level of their integration in the Turkish republic; Those Georgians who recognize Georgian language as their first language (realized as one of it’s dialect) define their national-ethnic identity and strive to protect their own dignity by using civilized methods and tools.